Influence of Different Seeding Dates on Fenugreek (Trigonella foenum-graecum L.) Forage Yield and Nutritive Value - A. Obour; E. Obeng; J. D. Holman (Kansas Agricultural Experiment Station Research Reports, 2015)
Fenugreek (Trigonella foenum-graecum L.) is used as medicinal plant in many Asian countries and has been reported to have forage quality similar to alfalfa. Fenugreek is an annual crop and may have the potential to diversify forage production systems in the central High Plains. This study evaluated forage dry matter (DM) production and the nutritive value of three fenugreek cultivars as influenced by planting date at Hays and Garden City, KS, in 2014. Results at Hays showed forage DM yield of fenugreek cultivars was not affected by planting date, but fenugreek cultivars differed significantly (P<0.05) in forage DM yield. Averaged across planting date, forage DM production was 760 lb/a for ‘Amber,’ 910 lb/a for ‘F96,’ and 672 lb/a for ‘Tristar.’ Forage crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), total digestible nutrient (TDN) concentrations, and relative feed value (RFV) did not differ (P>0.05) among fenugreek cultivars. Planting early, however, did increase CP levels and lower ADF and NDF concentrations. Despite the lower yields observed in 2014, our preliminary results showed that fenugreek can produce forage with nutritive value comparable to alfalfa and that further testing is needed to determine if fenugreek can provide an option for producers who want to diversify their forage production operations, particularly under limited irrigation conditions.
Keywords: fenugreek; forage quality; forage production